Path and boundary of the influence of social entrepreneurial opportunity identification on the growth of commercial startups - Junjie, Wu; Yawei, Zhang; Qiao Qiao, Ding (Frontiers in Environmental Science, 2022)
Social enterprise has emerged as the new mechanism to promote shared prosperity. The critical factor in driving the growth of social enterprises is identifying social entrepreneurship opportunities. How to realize the transformation from opportunity identification to social enterprise performance improvement has been a significant concern for the industry. We selected 177 social entrepreneurs as the research objects based on the social network theory. We utilized multiple regression analysis to explore how and when social entrepreneurship opportunity identification affects startup growth. The results show that finding opportunities for social entrepreneurship is a big part of how resource bricolage helps social businesses grow. The entrepreneurs' social network allows the mediating effect of resource bricolage. The more sources of "strong relationship" resources in the entrepreneurs' social network, the stronger the impact of social entrepreneurship opportunity identification on the growth performance of social enterprises. Our results provide new knowledge on the relationship between social entrepreneurship opportunity identification and startup growth from a social network perspective.